2009
DOI: 10.1007/s11738-009-0310-7
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical changes induced by increasing NaCl salinity in three fodder shrubs, Nitraria retusa, Atriplex halimus and Medicago arborea

Abstract: Nitraria retusa and Atriplex halimus (xero-halophytes) plants were grown in the range 0-800 mM NaCl while Medicago arborea (glycophyte) in 0-300 mM NaCl. Plants were harvested after 120 days of salt-treatment. The present study was designed to study the effect of salinity on root, stem and leaf anatomy, water relationship, and plant growth in greenhouse conditions. Salinity induced anatomical changes in the roots, stems and leaves. The cuticle and epidermis of N. retusa and A. halimus stems were unaffected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
41
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 48 publications
10
41
0
Order By: Relevance
“…Also, the slight increases (insignificant) in vegetative growth and flowering parameters of salt stressed plants due to nano silicon treatments are in agreement with those reported by Kalteh et al (2014) who found that nano silicon application increased leaves fresh and dry weights of basil salinity stressed plants. Furthermore, previous studies (Rahimi et al 2011;Bayat et al 2013 ;Mateos-Naranjo et al 2013;Gengmao et al 2015 andEsmaeili et al 2015) reported that application of Si in bulk materials (potassium silicate or sodium silicate) increased growth and flowering parameters of salt stressed ornamental plants.…”
Section: Interaction Between Effects Of Irrigation Water Salinity Andmentioning
confidence: 93%
See 2 more Smart Citations
“…Also, the slight increases (insignificant) in vegetative growth and flowering parameters of salt stressed plants due to nano silicon treatments are in agreement with those reported by Kalteh et al (2014) who found that nano silicon application increased leaves fresh and dry weights of basil salinity stressed plants. Furthermore, previous studies (Rahimi et al 2011;Bayat et al 2013 ;Mateos-Naranjo et al 2013;Gengmao et al 2015 andEsmaeili et al 2015) reported that application of Si in bulk materials (potassium silicate or sodium silicate) increased growth and flowering parameters of salt stressed ornamental plants.…”
Section: Interaction Between Effects Of Irrigation Water Salinity Andmentioning
confidence: 93%
“…Also, the results of increasing total chlorophylls in salinity stressed plants due to nano silicon application are in harmony with those reported by Kalteh et al (2014). Other studies (Bayat et al 2013 ;Mateos-Naranjo et al 2013;Gengmao et al 2015 andEsmaeili et al 2015) reported that application of Si in bulk materials (potassium silicate) resulted in increasing total chlorophylls or K% in salinity stressed plants.…”
Section: Chemical Constituentsmentioning
confidence: 97%
See 1 more Smart Citation
“…At the morphological level, NaCl alters morphological and anatomical characteristics of leaves and stems, such as leaf thickness, stem cross-section area or size and number of xylem vessels (Kilic ß et al 2007;Boughalleb et al 2009;Dolatabadian et al 2011). Whereas the relationship between salinity and morpho-anatomical plant responses has been explored to some extent, reports on the effects of alkaline or mixed salt-alkaline stresses are limited to few plant species, such as aspen (Mandre et al 2012), Pisum sativum (Gharsalli et al 2001), Catharanthus roseus (Cartmill et al 2008) and Phaseolus vulgaris (Valdez-Aguilar & Reed 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Bahia, as occurred during the vegetative growth under 20 mM NaCl (Table 2). Boughalleb et al (2009) studying two xerohalophyte and one glycophyte species reported that the sizes of xylem element vessels in the leaf's main vein were unaffected under salinity, but the number of vessels increased. This may be related to changes in IAA contents in salt-stressed plants, as IAA concentrations control xylem differentiation.…”
Section: Discussionmentioning
confidence: 99%